Educational qualifications and wage inequality: evidence for Europe - Budría, Santiago (2021)
In this paper we investigate the connection between education and wage inequality in nine European countries. We exploit the quantile regression technique to calculate returns to lower secondary, upper secondary and tertiary education at different points of the wage distribution. Using data from the last few decades, we describe changes in the conditional wage distribution of the surveyed countries. We find that in most European countries the amount of conditional wage dispersion within education groups is substantially higher and has grown faster among college-edu cated workers than among less educated workers